The Effect of Aromatherapy Inhalation on Reducing Chronic Pain for Children with Cancer: A Pilot Study - Triana, Komang Yogi; Allenidekania, Allenidekania; Hayati, Happy (Trends in Sciences, 2022)
Chronic pain is a physical symptom often experienced by pediatric patients with cancer. Long-lasting pain conditions can cause the deterioration of the quality of life of children. In order to enhance their quality of life, they should get any intervention to control the pain. Besides the pharmacologic pain management, nurses also should develop a non pharmacologic pain management strategy. One of the simplest and cheap strategy which is currently being developed was aromatherapy. This study aims to determine the effectiveness of aromatherapy for controlling chronic pain experienced by pediatric patients with cancer. The method used is a quasi-experiment with a consecutive sampling technique. There were 20 respondents involved, which were divided randomly into 2 groups. This study showed that inhaled aromatherapy proved effective for reducing chronic pain (p = 0.001) compared with standard care. Aromatherapy also have other positive effects that make the patient feel more relaxed and improve the patient’s sleep quality. Thus, the use of inhaled aromatherapy interventions can be considered to use in controlling the chronic pain experienced by pediatric patients with cancer to optimize the nursing care. However, further research is still needed by involving a larger number of respondents.